2021
DOI: 10.1002/mp.14994
|View full text |Cite
|
Sign up to set email alerts
|

The role of the construction and sensitive volume of compact ionization chambers on the magnetic field‐dependent dose response

Abstract: The magnetic-field correction factors of compact air-filled ionization chambers have been , investigated experimentally and using Monte Carlo simulations up to 1.5 T. The role of the nonsensitive region within the air cavity and influence of the chamber's construction on its dose response have been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…Figure1shows the geometry details and material information of the two detectors as implemented in the Monte Carlo code. The sensitive volume of the Semiflex 3D chamber derived using finite-element methods as described inDelfs et al (2021) was implemented. In addition to the 150 MeV protons as used during the experiments, the simulations were also done for incident proton energies of 60 MeV and 240 MeV.…”
mentioning
confidence: 99%
“…Figure1shows the geometry details and material information of the two detectors as implemented in the Monte Carlo code. The sensitive volume of the Semiflex 3D chamber derived using finite-element methods as described inDelfs et al (2021) was implemented. In addition to the 150 MeV protons as used during the experiments, the simulations were also done for incident proton energies of 60 MeV and 240 MeV.…”
mentioning
confidence: 99%
“…Further investigations into correction factors are required as shown by the limited data available on alternative chambers and differences between physically measured and simulated correction factors presented in Table 3 and 4 . Alternative dosimeters to standard reference ion chambers such as smaller volume chambers [ 72 ], microDiamond and microSilicon type detectors [ 73 ] have also been evaluated. Similar to conventional linacs, the output factors for small fields and the response of detectors under non-equilibrium conditions is an emerging area of research [ 74 ].…”
Section: Future Researchmentioning
confidence: 99%
“…the dose was scored in the active volume given in Figure 3 minus the slice of thickness d. The simple dead volume model from Malkov and Rogers seems to be adequate for the SNC chambers, since the guard ring is flat and fills the entire diameter of the chamber. Delfs et al 8 already investigated the SNC125c chamber and found that this form of guard ring does not produce a dead-volume. As the large SNC600c chamber has a very similar geometry, it was assumed that the simple model for the dead volume geometry is sufficient for the purpose of this study.…”
Section: Dead Volume Effectsmentioning
confidence: 99%
“…[1][2][3] The effect of magnetic fields on the response of ionization chambers has been investigated thoroughly in experimental and Monte Carlo studies on several chamber designs. [4][5][6][7][8][9][10][11] Its magnitude depends on chamber characteristics, such as the (effective) sensitive volume and material composition, but also on the magnetic field strength, the energy spectrum of the incident beam and the chamber orientation with respect to the magnetic field and beam directions. In most cases, large Farmer-type ion chambers were investigated under reference conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation